(untitled) (Research, Society and Development, 2021)
This article aimed to discuss the relationship of life experiences and trauma with hearing voices, and the content related to both. A qualitative study was carried out with 12 participants of a Virtual Self Help Group, from September to October 2020. Minayo’s thematic analysis was used to interpret the interviews, which resulted in two categories: (a) experiences of life and traumas related to the phenomenon of hearing voices and (b) content of voices and their relationship with trauma. Participants reported several events/situations in their lives that were related to their experience of hearing voices, such as sexual abuse, change of residence, institutional violence, harassment, family conflicts, abusive relationships, and bullying. Traumatic life situations, which are often avoided, subjectively repressed, tend to return as manifestations of the unconscious, whether in dreams, jokes, wrongdoings or as voices. This study identified that the voices heard by the participants are a reflection of emotions and feelings that remained latent. Thus, it is necessary to change the perspective on the pathological conditioning expended on this experience, to consider the situations and traumas experienced, in order to provide positive coping in the relationship with the voices. It is noteworthy the lack of studies that reflect on the need to explore the life history of these listeners and the relationship between trauma and the experience of hearing voices.